2020
DOI: 10.1111/ppe.12613
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐implantation urinary hormone monitoring distinguishes between types of first‐trimester spontaneous pregnancy loss

Abstract: Background Lutenising hormone (LH) and human chorionic gonadotropin (hCG) hormone are useful biochemical markers to indicate ovulation and embryonic implantation, respectively. We explored “point‐of‐care” LH and hCG testing using a digital home‐testing device in a cohort trying to conceive. Objective To determine conception and spontaneous pregnancy loss rates, and to assess whether trends in LH‐hCG interval which are known to be associated with pregnancy viability could be identified with point‐of‐care testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Based on sensitive urinary hCG measurements, several prospective observational studies reported miscarriage rates of approximately 30% in young women trying to conceive. [44][45][46][47] Most of these losses involve menstruation-like shedding of the endometrium 1-2 weeks after implantation and are, therefore, often not recognized clinically. The high attrition rate in the very early stages of pregnancy is widely attributed to embryonic aneuploidy, caused either by age-dependent meiotic errors in oocytes or age-independent erroneous mitotic divisions during preimplantation development.…”
Section: Discussionmentioning
confidence: 99%
“…Based on sensitive urinary hCG measurements, several prospective observational studies reported miscarriage rates of approximately 30% in young women trying to conceive. [44][45][46][47] Most of these losses involve menstruation-like shedding of the endometrium 1-2 weeks after implantation and are, therefore, often not recognized clinically. The high attrition rate in the very early stages of pregnancy is widely attributed to embryonic aneuploidy, caused either by age-dependent meiotic errors in oocytes or age-independent erroneous mitotic divisions during preimplantation development.…”
Section: Discussionmentioning
confidence: 99%
“…Based on sensitive urinary hCG measurements, several prospective observational studies reported miscarriage rates of approximately 30% in young women trying to conceive. 41–44 Most of these losses involve menstruation-like shedding of the endometrium one to two weeks after implantation and are therefore often not recognised clinically. The high attrition rate in the very early stages of pregnancy is widely attributed to embryonic aneuploidy, caused either by age-dependent meiotic errors in oocytes or age-independent erroneous mitotic divisions during pre-implantation development.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis echoes research suggesting declines in hCG can be noted even prior to other symptoms presenting 20 . There is also potential for this monitoring to occur prior to conception, with a recent study finding that a lag between the luteal phase and hCG production can be indicative of a biochemical pregnancy, possibly due to early or delayed implantation 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Tracking of hCG by pregnant women is practicable, as demonstrated by Foo et al who employed a fertility monitor that also provide semi-quantitative analysis of hCG levels on pregnancy tests that were used daily in women who conceived 21 . Retrospective analysis of the semi-quantitative data indicated that non-viable pregnancies had different hCG profiles to viable pregnancies.…”
Section: Discussionmentioning
confidence: 99%